Improving maternal and neonatal outcomes among pregnant women who are HIV-positive or HIV-negative through the Saving Mothers Giving Life initiative in Uganda: An analysis of population-based mortality surveillance data. - Maureen Nabatanzi; Julie R Harris; Phoebe Namukanja; Steven N Kabwama; Sandra Nabatanzi; Phoebe Nabunya; Benon Kwesiga; Alex R Ario; Patrick Komakech (Public Library of Science (PLoS), 2024)
HIV infection is associated with poor maternal health outcomes. In 2016, the maternal mortality ratio (MMR) in Uganda was 336/100,000, and the neonatal mortality rate (NMR) was 19/1,000. Saving Mothers, Giving Life (SMGL) was a five-year maternal and neonatal health strengthening initiative launched in 2012 in Uganda. We extracted maternal and neonatal data for 2015-2016 from the initiative's population-based mortality surveillance system in 123 health facilities in Western Uganda. We collected data on the facilities, HIV status, antiretroviral drug (ARV) use, death, birth weight, delivery type, parity, Apgar scores, and complications. We compared mother and baby outcomes between HIV-positive or HIV-negative, computed risk ratios (RR) for adverse outcomes, and used the chi-square to test for significance in differences observed. Among 116,066 pregnant women who attended and gave birth at SMGL-implementing facilities during 2015-2016, 8,307 (7.7%) were HIV-positive, of whom 7,809 (94%) used antiretroviral drugs (ARVs) at the time of delivery. During birth, 23,993 (21%) women experienced ≥1 complications. Neonate Apgar scores <7 (8.8%) and maternal haemorrhage during birth (1.6%) were the most common outcomes. Overall facility MMR was 258/100,000 and NMR was 7.6/1,000. HIV infection increased risk of maternal death (RR = 3.6, 95% Confidence Interval (CI) = 2.4-5.5), maternal sepsis (RR = 2.1, 95% CI = 1.3-3.3), and infant birth weight <2,500g (RR = 1.2, 95% CI = 1.1-1.3), but was protective against maternal complications (RR = 0.92, 95% CI = 0.87-0.97) and perinatal death (RR = 0.78, 95% CI = 0.68-0.89). Among the HIV-positive, ARV non-use increased risk of maternal death (RR = 15, 95% CI = 7.1-31) and perinatal death (RR = 2.3, 95% CI = 1.6-3.4). SMGL reduced facility MMR and NMR below national rates. HIV-infection was associated with maternal sepsis and death. Failure to use ARVs among women living with HIV increased the risk of maternal and perinatal death. Use of the SMGL approach and complementary interventions that further strengthen HIV care, may continue to reduce MMR and NMR.